Trends in Cancer Antigen 125 testing 2003‐2014: A primary care population‐based cohort study using laboratory data - Nicholson, B; Lee, M; Wijeratne, D; James, T; Shine, B; Oke, J (Wiley, 2018)
To understand Cancer Antigen 125 (CA125) testing in primary care in relation to a national guideline, we conducted a retrospective observational study including CA125 data from a well‐defined region in the UK, from 2003 to 2014. 51,033 CA125 tests from 30,737 women were stratified by month and year of testing, location of test request and patient age. Absolute numbers and rates of testing, rates and proportions of positive and negative tests, and frequencies of single and repeat tests were calculated. Negative binomial and logistic regression were used to test the effect of the guideline's introduction. Primary care testing spiked in the three months following the release of the guideline. However, there was no difference in the increase in testing observed across age groups. The proportion of positive tests decreased over time despite both the rates of positive and negative tests increasing. Retesting and repeat testing were associated with the initial CA125 value with no significant difference between women whose first test was 30–35 and >35 IU/L. Large studies using linked data are required to investigate the impact of increasing CA125 testing on onward intervention and patient outcomes. CA125 guidelines should be refined to avoid over‐investigation in low risk age‐groups.